Poor respiratory health outcomes associated with high illness worry and alexithymia: Eleven-year prospective cohort study among the working-age population - Selinheimo Sanna; Jokela Markus; Vasankari Tuula; Kanervisto Merja; Pirkola Sami; Suvisaari Jaana; Paunio Tiina (Elsevier, 2022)
Objective
Poor respiratory health outcomes have been associated with poorer physical health and higher psychological distress. The aim of this study was to investigate whether illness worry, alexithymia or low sense of coherence predict i) the onset of new respiratory disease, ii) respiratory symptoms or iii) lung function among the working-age population, independently of comorbidity mood-, anxiety, or alcohol abuse disorders.
Methods
The study was conducted among a nationally representative sample of the Finnish population (BRIF8901) aged 30–54 years (N = 2310) in 2000–2001 and was followed up in 2011. Individuals with a diagnosed respiratory disease or a severe psychiatric disorder at baseline were excluded. Lung function was measured by a spirometry test and psychiatric disorders were diagnosed using a structured clinical interview. Structured questionnaires were used to measure self-reported respiratory symptoms and diseases, illness worry, alexithymia, and sense of coherence.
Results
High illness worry predicted an 11-year incidence of asthma (OR 1.47, 95% CI 1.09–1.99, p = 0.01). Alexithymia predicted shortness of breath (OR 1.32, 95% CI 1.13–1.53, p < 0.01) and 11-year incidence of COPD (OR 2.84, 95% CI 1.37–5.88, p < 0.01), even after several adjustments for physical and mental health. Psychological dispositions did not associate with lung function in 2011.
Conclusions
In the general population, psychological factors that modify health behaviour predicted adverse respiratory health outcomes independently of lung function after 11 years of follow-up. This indicates that considering them part of personalized treatment planning is important for promoting health-related behaviour among the working-age population.